Community attitudes towards volunteering programs for community service "Prince Hussein Academy for Civil Protection as a model" - Al-Dalabih, Abdul-Razzaq Abdel-Hafez (Journal of Economic, Administrative and Legal Sciences, 2021)
The present study aimed to identify trends of ’attitudes towards volunteering programs directed at community service, and the study relied on the descriptive approach, and the study population consisted of a sample consisting of (81) academics at the Prince Hussein Academy for Civil Protection, chosen randomly, and the results showed the arithmetic averages of academics’ attitudes toward The volunteering programs directed to community service came with a moderate degree, with a mean (3.62) At the level of the paragraphs, the paragraph that says: "Volunteer work expresses the true values ​​that we believe in" was ranked first, with an arithmetic average (4.10) and a high level, while the paragraph that states: "Free invest time in volunteer work." With an average of (3.16) and a medium degree, the results showed that there are no differences in academics ’attitudes towards volunteer programs directed to community service due to the variable of academic experience, while the results showed the existence of differences attributed to: the faculty variable and in favor of human faculties and in light of the results of the study recommend the need to link enrollment With the voluntary programs in the promotion system to encourage academics to practice volunteer activities in the local community.
Keywords: volunteer work; attitudes; community service